Resistência aos antimicrobianos, diversidade e relação epidemiológica de bactérias do gênero Salmonella spp isoladas na granja de terminação e abate de suínos - Guimarães, Adélia Rodrigues (2010)
Salmonella spp. constitute an important zoonotic pathogen that may be disseminated widespread in the pork production chain. Its presence in the meat of these animals is cause of concern to slaughterhouses and a risk to human health. Eighty six samples of Salmonella spp. were used, previously isolated from the pork production chain, from 90 samples of swine feces, 135 carcasses and 24 environmental samples. The objective of this study was to determine the antimicrobial resistance, to identify the serotypes and to establish the phylogenetic relationship among them through RAPD-PCR technique. The serological identification was previously performed through O-somatic polyvalent antiserum and B, C and D monovalent ones, and concomitantly, the definite antigenic characterization tests were undertaken in official laboratory. The antimicrobial resistance was determined through disk diffusion antibiotic sensitivity testing, and the phylogenetic similarity among isolate samples through RAPD-PCR technique. The identified serotypes as follows: Typhimurium (32.55%), Agona (23.26%), Infantis (19.77%), Minnesota (17.44%) and Panama (6.98%). The dendrograms demonstrated homology among isolate samples from different serotypes grouped in clusters. The similarity was independent from the place of isolation confirming the presence of clones along the production chain. They also indicated swine that excrete Salmonella Typhimurium in feces contribute to the contamination of carcasses and to the cross contamination, and the slaughtering conditions limited the survival of Salmonella Agona. In regard to those two serotypes, the animal feed was probably the primary source of animal infection within the farm. Contamination was observed in the pork s epilator, where the same clone of Salmonella Minnesota identified in swine feces was present, but there were no isolate samples among carcasses. Salmonella Panamá among carcasses is apparently not related to the previous infection of animals. Isolate samples of Salmonella Infantis in swine feces were related to tenvironmental infection of the farm or to the infection during anterior stages in relation to finishing animals. Multiresistance pattern to antimicrobials was observed in all serotypes tested, being more than 50% with resistance to nine out of the eleven tested antibiotics. The most effective drugs were the Sulfazotrim and the Norfloxacin, with resistance from 16.3% to 54.6%, respectively. Salmonella Minnesota and Salmonella Infantis presented the most elevated pattern of resistance to Sulfazotrim. The results of this study demonstrated the necessity of monitoring the antimicrobial resistance of zoonotic bacteria and the implantation of more effective manners to control the presence and persistence of Salmonella along the pork production chain as a way to guarantee the innocuity of food and consumer safety.